2021
DOI: 10.1111/ajr.12799
|View full text |Cite
|
Sign up to set email alerts
|

Importance of attachment to place in growing a sustainable Australian Rural Health Workforce: A rapid review

Abstract: Introduction: Personal, community, and environmental factors can influence the attraction and retention of regional, rural, and remote health workers.However, the concept of place attachment needs further attention as a factor affecting the sustainability of the rural health workforce. Objective:The purpose of this rapid review was to explore the influence of a sense of place in attracting and retaining health professionals in rural and remote areas.Design: A systematic rapid review was conducted based on an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Consistent with previous studies [ 5 , 64 ] feeling welcomed and connected to the community was reported to be important in this review. Some allied health professionals discussed feeling welcome and included in the local community, while others reported it was challenging to get to know people, to feel involved and to find out what activities were available within the community.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies [ 5 , 64 ] feeling welcomed and connected to the community was reported to be important in this review. Some allied health professionals discussed feeling welcome and included in the local community, while others reported it was challenging to get to know people, to feel involved and to find out what activities were available within the community.…”
Section: Discussionsupporting
confidence: 90%
“…Research continues to highlight regional Australia's challenge to attract and retain healthcare workers (Buykx et al, 2010). With respect to the present research, there is evidence that sense of place and community may influence health workers' decisions to work and develop their careers in a rural community (Beccaria et al, 2021;Cosgrave, 2020b;Cosgrave et al, 2019;Malatzky et al, 2020).…”
Section: Place Attachment and Identitymentioning
confidence: 77%
“…Not only did students have limited opportunities to engage with other students and clinicians at placement sites and accommodation facilities, but they were also unable to immerse themselves in the local community and build physical connections with the local area, all of which are important for the development of a sense of place, rural practice and community engagement. 27 , 28 Importantly, this sense of disconnection between rural and remote communities was amplified for students who undertook a virtual rural or remote placement experience, where they remained at home and delivered services remotely via telehealth. This finding is similar to Mak et al 11 who found that virtual placement experiences allow students to achieve clinical learning outcomes, but were not as effective in facilitating their affective and physical learning about the rural location.…”
Section: Discussionmentioning
confidence: 99%